Makna Idiomatikal Idiom Pada Manga One Piece Vol. 91 Karya Eiichiro Oda - Ikhsan Maulana Fadlilah; Anisa Arianingsih; Soni Mulyawan Setiana (Janaru Saja: Jurnal Program Studi Sastra Jepang (Edisi Elektronik), 2020)
This study aims to describe the meaning of idioms in the manga One Piece Vol. 91 which is one of the popular manga with a high frequency of idioms. The method used in this research is descriptive analysis method. The results of this study found 13 idioms which is ki ga tsuku means "sober" or "conscious", hara no mushi means "stomach sound", akke ni torareru means "very surprised", ki ni suru means "worried", mi o hiku means "retreat", ude ni oboe ga aru means "confident", ki ga aru means "interested", sumi ni okenai means "great", mentsu ga tatsu means "maintain reputation" , te o dasu means "fighting", uma no hone means "someone whose identity is unknown", kuchi ni suru means "saying", and hedo ga deru means "fed up". The author hopes that further research can examine idioms in grammatical terms.